Silent embolization of an Amplatzer septal occluder into the left ventricular outflow tract requiring emergent surgical retrieval - Abdelkarim Errahmouni; Mustapha El Hattaoui; Abdennasser Drighil; Drissi Boumzebra (Annals of Pediatric Cardiology, 2012)
Percutaneous closure of secundum atrial septal defect is an established safe alternative to surgery with rare complications and high primary success rate. This procedure can be complicated by early or late device embolizations. We report an asymptomatic delayed nonobstructive embolization of an amplatzer septal occluder (ASO) into the left ventricle outflow tract detected by routine transthoracic echocardiography 1 week after implantation, which required emergent surgical retrieval in a stable patient.